Moral Disengagement Mechanisms and Armed Violence. A Comparative Study of Paramilitaries and Guerrillas in Colombia (2018)
Moral disengagement mechanisms are strategies to make immoral actions appear moral. This study explores their us-age by two Colombian illegal armed groups (guerrillas and paramilitaries), as well as differences between the groups. The analysis covered 367 communiqués issued in 55 months. A deductive content analysis revealed that the most used mechanisms were: attribution of blame, euphemistic labeling, moral justification and labeling with undesirable names. Results showed differences between groups only in the number of press releases, but not in frequency or type of the mechanisms used. The findings are analyzed in the discussion section in relation to the theory of dissonance, extreme violence and motives for joining illegal armed groups.